Aplikasi Metode Jaringan Syaraf Tiruan Backpropagation dalam Meramal Tingkat Inflasi di Indonesia - Saluza, Imelda (GRADIEN : Jurnal Ilmiah MIPA, 2015)
Inflation is one of the important indicators in analyzing the economy of a country. One aspect that could detect the stability of Rupiah, the Indonesian Currency, is reflected in low inflation and stability. Furthermore, in determining a country’s rate of inflation for a period ahead, time series forecasting could be used as one alternative. Forecasting is a statistical method which plays an important role in delivering a decision. Forecasting the future based on past information from a variable or past mistakes is called time series. The inflation rate is one of financial data, which tends to be non linear and volatile. Therefore, neural network forecasting is used.